Natural product Erianin: mitigating FOLFOX toxicity and enhancing against colorectal cancer - Yang, Fuqin; Li, Zeqiao; Zhang, Haishan; Zhang, Mingxiao; He, Zhenwei; Zheng, Xiaoqin; Zhu, Yingru; Long, Pei; Ding, Ruirui; Lin, Zhengbin; Deng, Lijuan (Frontiers in Chemistry, 2025)
IntroductionColorectal cancer (CRC) is a prevalent malignant tumor of the digestive tract. The FOLFOX regimen (oxaliplatin + calcium folinate + 5-fluorouracil) serves as the primary treatment for advanced CRC clinically, yet its application is significantly limited by substantial toxic side effects. Erianin, a natural compound from Chinese medicine Dendrobium chrysotoxum Lindl, demonstrates significant potential in both tumor growth inhibition and chemotherapy toxicity reduction. This study aims to investigate the potential of Erianin in reducing the toxicity of the FOLFOX regimen while enhancing its antitumor efficacy.MethodsThis study integrated network toxicology and molecular docking to predict the potential targets of Erianin in alleviating FOLFOX-induced side effects. Using an orthotopic MC38 CRC transplantation model, we conducted a comprehensive evaluation of the effects of Erianin in mitigating FOLFOX-induced changes in body weight changes, hematological parameters, and histopathology of major organs (heart, liver, spleen, kidneys, and intestines). IHC analysis elucidated alterations in intestinal barrier proteins, AKT1/mTOR pathway, and tumor proliferation and apoptosis biomarkers. Tumor progression was dynamically monitored by in vivo imaging.ResultsThe results showed that Erianin improved weight loss, pathological changes in organs, and reduction in peripheral blood cell counts (WBC, RBC, HGB, PLT, HCT) caused by FOLFOX in mice. Erianin reversed the inhibition of intestinal tight junction proteins (e.g. ZO-1, Occludin, Claudin-5) and AKT1/mTOR pathway caused by FOLFOX. In addition, the tumor size was significantly reduced in the combination group, and the expression of the apoptosis marker Cleaved Caspase-3 was up-regulated, and the proliferation markers Ki67/PCNA were down-regulated.DiscussionErianin can enhance the anti-CRC effect of FOLFOX, and mitigates FOLFOX-induced toxicity by activating the AKT1/mTOR pathway.